Between baroque splendor and political pragmatism – the content and form of the Karlowitz Treaty documents and the course of its ratification between Warsaw and Istanbul - Kołodziejczyk, Dariusz (Balcanica Posnaniensia. Acta et studia, 2003)
The Treaty of Karlowitz of 1699, ending the sixteen-year conflict between the Ottoman Empire and the Holy League, is considered in historiography to be the symbolic end of Ottoman hegemony in Central and Eastern Europe and the beginning of a new diplomatic order. Despite its significance, little attention has been paid in academic research to the treaty documents themselves, their form, content, and the practice of their exchange and ratification. The aim of the article is to analyse the documents of the Treaty of Karlowitz, both Ottoman and Polish, from the perspective of their content, diplomatic form, and ratification procedures. The author attempts to verify to what extent the treaty actually represented a new model of international relations and to what extent it continued older Ottoman diplomatic patterns, including the idea of sultanic unilateralism. The study is based on a wide range of manuscript and printed sources, including unpublished originals of treaties preserved in Polish archives, Ottoman diplomatic documents, ambassadorial reports, and an analysis of mediation documents. Contemporary eyewitness accounts and materials from foreign archives were also used. The conclusions emphasise that although the Treaty of Karlowitz showed elements of modern congress diplomacy (e.g. the participation of intermediary states), traditional forms dominated in Ottoman documents. The Porte's resistance to the first act of ratification sent by Augustus II was not only formal but also political – it expressed distrust of attempts to centralise power in Poland on the Saxon model. The final ratification and issuance of Sultan Mustafa II's „letter of alliance” sealed the recognition of the equality of the parties, although it was couched in conservative Ottoman diplomatic rhetoric.